A new approximate solution of the fuzzy delay differential equations. (29th April 2019) - Jameel, A.F.; Anakira, N.R.; Alomari, A.K.; Al-Mahameed, M.; Saaban, A.
In this paper, an approximate analytical algorithm namely homotopy analysis method (HAM) is presented for the first time to obtain approximate analytical solutions of first order fuzzy delay differential equations (FDDEs). This method allows for the solution of the FDDEs to be calculated in the form of an infinite series with the components that can be easily calculated. The HAM utilises a convergence control parameter the convergence region of the infinite series solution. Numerical examples are tested to highlight the important features of the HAM algorithm.